2013
DOI: 10.1186/1475-2891-12-77
|View full text |Cite
|
Sign up to set email alerts
|

An observational study reveals that neonatal vitamin D is primarily determined by maternal contributions: implications of a new assay on the roles of vitamin D forms

Abstract: BackgroundVitamin D concentrations during pregnancy are measured to diagnose states of insufficiency or deficiency. The aim of this study is to apply accurate assays of vitamin D forms [single- hydroxylated [25(OH)D2, 25(OH)D3], double-hydroxylated [1α,25(OH)2D2, 1α,25(OH)2D3], epimers [3-epi-25(OH)D2, 3-epi-25(OH)D3] in mothers (serum) and neonates (umbilical cord) to i) explore maternal and neonatal vitamin D biodynamics and ii) to identify maternal predictors of neonatal vitamin D concentrations.MethodsAll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
70
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 21 publications
5
70
2
2
Order By: Relevance
“…Past studies have analysed neonatal 25OHD determinants [8,9]. A study of 60 mother-baby dyads in Greece generated a model predicting 56% of neonatal 25OHD [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies have analysed neonatal 25OHD determinants [8,9]. A study of 60 mother-baby dyads in Greece generated a model predicting 56% of neonatal 25OHD [8].…”
Section: Discussionmentioning
confidence: 99%
“…A study of 60 mother-baby dyads in Greece generated a model predicting 56% of neonatal 25OHD [8]. Maternal characteristics, including UVB exposure, explained 12.2% of variance, while maternal 25OHD levels and vitamin D epimers accounted for 44%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In infants, a 3-epi isomer of 25(OH)D 3 has been identified to occur in concentrations that are significantly elevated as compared to older 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 children and adults [3e7]. This elevation complicates the interpretation of 25(OH)D 3 concentrations as it may be erroneously included in the total 25(OH)D 3 by Liquid Chromatography-Mass Spectrometry methods that are unable to distinguish between the chiral compounds [8,9]. The 3-epimer of 1a,25-(OH) 2 D 3 , the presumed active form of 3-epi-25(OH)D 3 , has been shown to have a lower affinity for the vitamin D receptor than 25(OH)D 3 , suggesting that it's biological activity may be lower [10].…”
Section: Introductionmentioning
confidence: 98%
“…While previous data indicated that neonatal and infant vitamin D stores are reliant from maternal ones [3], routine accurate measurement of epimers could overcome the technical flaws provoked by the presence of a significant percentage of epimers as a fraction of total vitamin D levels.…”
mentioning
confidence: 98%